2020
DOI: 10.1200/jco.2020.38.5_suppl.41
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of anti-ROR1 CAR T cells employing a ROR1 binding SCFV derived from the clinical stage mab cirmtuzumab.

Abstract: 41 Background: Chimeric antigen receptor (CAR)-modified T cells (CAR-T) were generated targeting cells expressing ROR1, which is present on many malignant cancers and has been associated with cancer stemness and chemo-resistance. The ROR1 CAR utilizes the humanized single-chain fragment variable (scFv) binding domain of UC-961 (cirmtuzumab), which exhibits high affinity and specificity for human ROR1 and has demonstrated an excellent safety profile in Phase 1 studies. Methods: CAR constructs with varying spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hudecek et al reported the first ROR1-targeted CAR-T cell with cytotoxicity in CLL and MCL cells [ 96 ] . More recently, Prussak et al reported on a ROR1-specific CAR T-cell that effectively and selectively killed ROR1-containing lymphoid cancer cells in mice [ 98 ] .…”
Section: Strategies For Overcoming Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Hudecek et al reported the first ROR1-targeted CAR-T cell with cytotoxicity in CLL and MCL cells [ 96 ] . More recently, Prussak et al reported on a ROR1-specific CAR T-cell that effectively and selectively killed ROR1-containing lymphoid cancer cells in mice [ 98 ] .…”
Section: Strategies For Overcoming Resistancementioning
confidence: 99%
“…While ROR1 is highly expressed in undifferentiated embryonic stem cells, it is not found in other adult tissue types except for a low expression in adipose tissue [96] . Additionally, higher levels of ROR1 on CLL cells are associated with more aggressive disease, and its expression remains stable across progression and treatment [97] . Therefore, it presents an attractive prospect for achieving highly targeted effects, thereby mitigating adverse events and reducing immunosuppression.…”
Section: Ror1mentioning
confidence: 99%
“…Thus, it is an attractive target for CAR T cell therapy, as it has the potential to improve specificity, efficacy, and reduce side effects of such a B-cell depletion and hypogammaglobulinemia related to treatment. In preclinical models of CLL, ROR1 CAR T-cells demonstrated selective toxicity for ROR1 expressing leukemia cells, with rapid clearance of leukemia cells in vivo [ 58 ]. A phase 1 clinical trial (NCT02706392) of ROR1 CAR T-cells for patients with both hematologic and solid tumors is currently underway.…”
Section: Strategies To Improve Car T Cell Therapy For Patients With Cllmentioning
confidence: 99%